2004
DOI: 10.1108/00242530410531857
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in library anxiety among graduate students

Abstract: This study compared the five subscale scores and total scale scores of the Library Anxiety Scale from 135 Caucasian‐American and 45 African‐American graduate students. Findings indicated that the Caucasian‐American sample reported significantly higher levels of library anxiety associated with three of the five subscales than did the African‐American sample. A canonical discriminant analysis also revealed significant differences between the two racial groups, with Caucasian‐American graduate students reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Results of the current study also indicated that the educational intervention could not affect the anxiety caused by technical barriers. This type of anxiety results from different factors such as limited number of computers, lowspeed internet, rapid changes in library technologies, fear of destroying the machinery, and technical terms related to the computer and Internet (18). Such type of information seeking anxiety is mostly associated with technical barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the current study also indicated that the educational intervention could not affect the anxiety caused by technical barriers. This type of anxiety results from different factors such as limited number of computers, lowspeed internet, rapid changes in library technologies, fear of destroying the machinery, and technical terms related to the computer and Internet (18). Such type of information seeking anxiety is mostly associated with technical barriers.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated African American graduate students at historically Black colleges and universities and Caucasian graduate students at predominantly Caucasian-populated institutions. Findings suggested that African American students have lower library anxiety than Caucasian students (Jiao et al, 2004). This study was replicated to ensure validity in 2006.…”
Section: Library Anxiety and Race Researchmentioning
confidence: 91%
“…Bostick (1992) also developed the Library Anxiety Scale, a 43-item Likert scale to test the five areas of library anxiety in undergraduates. Many subsequent quantitative studies found that library anxiety is influenced by barriers with staff (e.g., Karim & Ansari, 2010), race (e.g., Jiao, Onwuegbuzie, & Bostick, 2004, year of study, gender, native language (e.g., Jiao, Onwuegbuzie, & Lichtenstein, 1996), and structured learning styles (e.g., Onwuegbuzie & Jiao, 1998). In addition, researchers found no significant relationship between library anxiety and trait anxiety (Jiao & Onwuegbuzie, 1999).…”
Section: Library Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…They are more likely to pretend to know everything rather than ask the library staff for help. Jiao, Onwuegbuzie and Bostick (2004) noted that library anxiety may occur from a lack of confidence while doing the research in the library or lack of exposure to library facilities and services. It clearly shows that students with inadequate exposure of the library are more likely to be anxious when using it.…”
Section: Introductionmentioning
confidence: 99%